Perinatal Exposure to Tartrazine Triggers Oxidative Stress and Neurobehavioral Alterations in Mice Offspring - Gadah Albasher; Najla Maashi; Saleh Alfarraj; Rafa Almeer; Tarfa Albrahim; Fatimah Alotibi; May Bin-Jumah; Ayman M. Mahmoud (MDPI AG, 2020)
The use of synthetic azo dyes as coloring agents in food products has dramatically increased. This study evaluated the effect of perinatal exposure to tartrazine (TZ) on mice offspring, focusing on neurobehavioral alterations and oxidative stress. The female mice received TZ (2.5 and 5 mg/kg) via oral gavage during pregnancy and the first 15 days after birth. At days 21 and 35 after birth, male mice were sacrificed, and samples were collected for analyses. Perinatal exposure to TZ triggered tissue injury evidenced by the histological alterations and neuronal damage in the cerebrum, medulla oblongata, and cerebellum. TZ provoked lipid peroxidation and diminished cellular antioxidants in different brain regions of the newborns. In addition, TZ increased hemoglobin content, as well as erythrocytes, leukocytes, and platelets count at days 21 and 35 after birth. Both the locomotor behavior and anxiety reflex were significantly altered in mice exposed to TZ. In conclusion, perinatal exposure to TZ within an adequate daily intake range induced oxidative stress and neurobehavioral and hematological alterations in mice offspring. Therefore, consuming foods containing TZ during pregnancy and lactation warrants public awareness.